Awareness and Practice of Renal Dose Adjustment Guidelines among Doctors: A Survey-Based Study (International Journal of Scientific Research in Science and Technology, 2025)
Background: Renal dose adjustment is vital for patient safety, particularly in those with impaired kidney function. This study assesses doctors’ awareness, practices, and perceived barriers across specialties. Objective: This study assesses doctors’ awareness and practices related to renal dose adjustment using a structured questionnaire-based analysis. Methods: A cross-sectional survey of 40 doctors from various departments gathered data on clinical experience, renal dosing practices, references used, and perceived responsibilities and barriers. Results: Among the 40 respondents, over 80% recognized the importance of renal dose adjustment, and about 70% routinely considered eGFR or creatinine clearance. More than 75% agreed that all renally excreted drugs should be adjusted, yet only 30% had received formal training or CME. The most cited barrier was a lack of updated knowledge. Lexicomp and Medscape were the preferred references. While most used renal dosing in emergencies, nearly half limited it to specific drugs. Conclusion: Doctors show moderate awareness of renal dose adjustment, but knowledge gaps and limited training remain key barriers. Improving education, involving clinical pharmacists, and encouraging use of trusted references can enhance safe prescribing in renal impairment.